2022
DOI: 10.1097/cji.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

B2M and JAK1/2–mutated MSI-H Colorectal Carcinomas Can Benefit From Anti-PD-1 Therapy

Abstract: β2-microglobulin (B2M) and Janus kinases 1 and 2 (JAK1/2) mutations have been suggested as genetic mechanisms of immune evasion for anti-programmed cell death protein 1 (PD-1) therapy. Whether B2M and JAK1/2 lose-of-function mutation can cause primary resistance to anti-PD-1 therapy in colorectal carcinoma (CRC) patients remains controversial. Here, we sought to compare the efficacy of anti-PD-1 therapy in DNA mismatch repair deficient/microsatellite instability-high CRC patients with or without B2M or JAK1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A study by Yang et al found that B2M mutation was an indicator of immunotherapy resistance in pan-cancer species [9]. While Ding et al con rmed that immunotherapy resistance-related gene B2M mutation did not affect the bene t of MSI-H colorectal cancer patients from anti-PD1 immunotherapy [10]. Meanwhile, the patient refused any kind of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yang et al found that B2M mutation was an indicator of immunotherapy resistance in pan-cancer species [9]. While Ding et al con rmed that immunotherapy resistance-related gene B2M mutation did not affect the bene t of MSI-H colorectal cancer patients from anti-PD1 immunotherapy [10]. Meanwhile, the patient refused any kind of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy and adjuvant chemotherapy significantly improve survival of several cancers, and the immunotherapies by targeting immune check points, are successfully used in certain cancers ( 27 29 ). In this study, we could not analyze these important aspects of multimodal and novel therapies, as there was not sufficient information available.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a recent meta-analysis, BRAF mutations do not influence the response to ICI, while remaining a negative prognostic biomarker [ 236 ]. The association between oncogenic mutations with ICI resistance in MSI CRC was not confirmed for B2M , HLA , and JAK1/2 , although these genes were found to be frequently mutated in MSI CRC [ 46 , 47 ].…”
Section: Mechanisms Of Resistance To Icimentioning
confidence: 99%
“…At the same time, about a quarter of metastatic colorectal cancers and up to half of some other types of cancer are intrinsically resistant to ICI [ 43 , 44 ]. Several mechanisms of such an intrinsic resistance have been proposed, including the activating mutations in the RAS/RAF signaling pathway [ 45 ], mutations in the antigen presentation machinery and interferon pathway genes [ 46 , 47 ], establishment of an immunosuppressive microenvironment [ 48 ], as well as the influence of the gut microbiome [ 49 ] and immunoediting theory [ 50 ].…”
Section: Introductionmentioning
confidence: 99%